2015
DOI: 10.1007/s10661-015-4776-z
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater runoff to an impaired lake: impacts and solutions

Abstract: Stormwater runoff can represent a significant source of pollutants to downstream water bodies. An integrated assessment was conducted for the Spring Lake watershed in western Michigan because of concerns that increased impervious land cover in the watershed, especially in sub-basins adjacent to Spring Lake, would result in greater stormwater runoff and pollutant loads. Spring Lake has a history of high total phosphorus (TP) concentrations and cyanobacterial blooms. An alum treatment, paid for by an assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
6
0
2
Order By: Relevance
“…Results from the majority of studies suggest that implementation of SCMs reduces mass export of dissolved (e.g., soluble reactive phosphorus [SRP] and nitrate) and particulate (e.g., total suspended solids and total phosphorus) pollutants and that the primary mechanism underlying these patterns is hydrological rather than biogeochemical (Table ). Monitoring SCM implementation over time at the watershed scale, for both detention‐ and infiltration‐based networks, shows that pollutant load reductions are frequently tied to reductions in run‐off generation (Ahiablame et al, ; Dietz & Clausen, ; Hale et al, ; Selbig & Bannerman, ; Steinman et al, ). For example, Bedan and Clausen () observed significant reductions to peak discharge and total flow volume in an LID watershed, which translated to load reductions for nitrate (NO 3 − ) and total Kjedahl nitrogen, compared to a watershed with no SCMs.…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the majority of studies suggest that implementation of SCMs reduces mass export of dissolved (e.g., soluble reactive phosphorus [SRP] and nitrate) and particulate (e.g., total suspended solids and total phosphorus) pollutants and that the primary mechanism underlying these patterns is hydrological rather than biogeochemical (Table ). Monitoring SCM implementation over time at the watershed scale, for both detention‐ and infiltration‐based networks, shows that pollutant load reductions are frequently tied to reductions in run‐off generation (Ahiablame et al, ; Dietz & Clausen, ; Hale et al, ; Selbig & Bannerman, ; Steinman et al, ). For example, Bedan and Clausen () observed significant reductions to peak discharge and total flow volume in an LID watershed, which translated to load reductions for nitrate (NO 3 − ) and total Kjedahl nitrogen, compared to a watershed with no SCMs.…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
“…When distributed rain gardens at the household level were added to the simulation, little further reductions were observed. Models have also been used to optimize pollutant removal and cost (Liu, Chen & Peng, 2015) and to determine most acceptable areas for siting of SCMs based on biophysical and societal constraints (Lee et al, 2012;Martin-Mikle et al, 2015;Steinman et al, 2015).…”
Section: Cumulative Effects Of Scms On Water Qualitymentioning
confidence: 99%
“…This study demonstrated that varying EMCs during calibration can improve model performance (Figures 5 and ; Table 2). Incorporating generic EMCs and treating them as a static input parameter is a common modeling practice (Steinman et al 2015; Fisher et al 2016; Alamdari et al 2017). In this study, applying the PADEP EMCs would have resulted in significant underestimation of TSS loads in stormwater and incorrect representation of settling and resuspension within the stream.…”
Section: Stormwater Tss Results and Emc Calibrationmentioning
confidence: 99%
“…The main sources of pollutants from daily operation identified were: wooden sleepers, herbicides, fueling and lubrication, wear and tear processes and corrosion resistant poles, embankment materials and human activities. A six steps novel approach was provided by Steinman et al (2015) to identify priority areas and subsequently reduce nonpoint source of pollution for the Spring Lake watershed in western Michigan. A best suited management practice was identified to be placed in the watershed and their optimal locations were assessed to model the degree to which their implementation would reduce TP and TSS.…”
mentioning
confidence: 99%